From classroom to classZoom: Participation and engagement in an online environment - Murphy, Aurora; Nixon, Deborah; Yeo, Joseph (Journal of Academic Language and Learning, 2022)
Student participation and engagement are central to learning, yet behaviours that indicate participation and cognitive engagement can differ in online and face-to-face classes. This difference became apparent in 2020, when universities around the world transitioned from face-to-face classrooms to wholly online classes. With this move, tutors’ perceptions of participation and engagement changed. Based on written reflections by 13 tutors who teach at an Australian university, we found that tutors recognised new/different indicators of engagement in the classZoom. In addition, the tutors observed that issues around student diversity and access greatly influence how students participate in the classZoom. Tutors also learnt not to assume that students were not participating and engaging online if they did not enact the same behaviours expected of them in face-to-face classes. Using active learning theories, this paper argues that participation and engagement can be understood and fostered online with particular attention to student diversity and digital access. These understandings enrich current pedagogical perceptions and inform educators to ‘design in’ more active forms of engagement in the classZoom. What has been learnt through this experience has salience beyond the confines of COVID lockdowns and into hybrid modalities of online and face-to-face teaching practices.